Analisis Komparatif Terhadap Efektifitas Mediasi Berdasarkan Perma Nomor 1 Tahun 2016 dan Perma Nomor 3 Tahun 2022 (Studi Kasus di Pengadilan Agama Tanjungpandan Kelas 1B): (Studi Kasus di Pengadilan Agama Tanjungpandan Kelas 1B) - Alfadiah, Cut Nadita; Anwar, Reski; Hajrianto, Anugrah; Ikrom, Muhammad; Muslim, Muhammad (ISLAMITSCH FAMILIERECHT JOURNAL, 2025)
Due to the Covid-19 outbreak, which has expanded to remote parts of Indonesia, the Supreme Court was compelled to issue Supreme Court Regulation No. 3 of 2022, an article pertaining to mediation, in addition to The supreme court Regulation No. 1 of 2016. The point of view of mediation efficiency is where there is a notable difference.. This research aims to determine which mediation is greater effective to carry out at the Tanjungpandan Class 1 B Religious Court. Descriptive qualitative research techniques are used in this study with a normative nature a juridical approach conducted using literacy-based literature studies and interviews. Final results of this research shows that face-to-face mediation based on Supreme Court Regulation No. 1 of 2016 is considered more effective than Electronic mediation in accordance with Supreme Court Rule No. 3 of 2022. Because it is considered more efficient and easier to understand. Apart from the birth article Regulation No. 3 of 2022 of the Supreme Court since of the appearance of Covid-19, Digital Mediation is not considered mandatory mediation, but rather an alternative. According to the guidelines in the third clause of Supreme Court Rule No. 3 of 2022. Due to the many shortcomings experienced when Electronic Mediation is implemented. Even so, it could be in the future Electronic Mediation will be in the spotlight, this is driven by technological developments and is considered to better support the Mediation process at a low cost, quickly and simply. Keyword: Mediation, Effectiveness, Religious Courts